Fingerprinting postblast explosive residues by portable capillary electrophoresis with contactless conductivity detection. Issue 8 (7th February 2014) - Kobrin, Eeva‐Gerda; Lees, Heidi; Fomitšenko, Maria; Kubáň, Petr; Kaljurand, Mihkel
<x xml:space="preserve">Abstract</x> A portable capillary electrophoretic system with contactless conductivity detection was used for fingerprint analysis of postblast explosive residues from commercial organic and improvised inorganic explosives on various surfaces (sand, concrete, metal witness plates). Simple extraction methods were developed for each of the surfaces for subsequent simultaneous capillary electrophoretic analysis of anions and cations. Dual‐opposite end injection principle was used for fast (<4 min) separation of 10 common anions and cations from postblast residues using an optimized separation electrolyte composed of 20 mM MES, 20 mM l‐histidine, 30 μM CTAB and 2 mM 18‐crown‐6. The concentrations of all ions obtained from the electropherograms were subjected to principal component analysis to classify the tested explosives on all tested surfaces, resulting in distinct cluster formations that could be used to verify (each) type of the explosive.